Metadados para o uso de ferramentas de gestão de dados de investigação com investigadores do I3S - Marcelo da Costa Sampaio (2019)
In the last decades, the research data production has been growing a lot, mainly due to the technological development which has transformed the entire workflow of the researchers. This situation creates challenges regarding research data management activities, especially at the level of analysis, storage, preservation and sharing of these research data. Research data management is essential to scientific practice and there are many stakeholders involved in the different stages of this process researchers, funding agencies, universities, curators who care about the value of the produced data. In the field of research data management, it is also important to support researchers with tools that simplify their work in managing research data. Electronic research management tools are important as they enable researchers to meet the RDM requirements and create a bridge between the different stages in the flow of research data management. Their adoption can help controlling the data life cycle since it is possible to store the data and associate it with metadata in order to make it FAIR - Findable, Accessible, Interoperable, Reusable. In addition, its integration with research data repositories is also essential as it allows the indexing, preservation and availability of data for the scientific community. In order to support the researchers in their research data management tasks, in this this study we collaborate with a group of researchers from the Institute of Research and Innovation in Health (I3S) in order to test and evaluate Dendro platform, developed in FEUP and INESC TEC, as well as to validate a metadata descriptors model developed specifically for the researchers domain. The results obtained from the researchers feedback show that the developed model favours an easy entry point in the data description tasks but does not prevent researchers from presenting its limitations and identifying their specific requirements.